Complexity, Maturity and Competency in the Project Risk Management Environment: A Relational Framework involving the Triple Helix Role Players - et. al., E Naidoo, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The growth in project activity and rise in project failures emphasises the importance of project management as a discipline in which employee perceptions, knowledge, decision-making and communication play a central role. This is even more apparent when projects affect not only one facet of society, but have far reaching consequences for government, industry and training providers. This paper aims to ascertain whether there is a relationship between complexity, maturity and competence with respect to projects. A multi-method research approach was employed, whereby interviews and a web-based survey were used to collect data from Eskom management and project risk management practitioners. The data and information were used to develop a sense-making framework and propose recommendations to enhance project risk management, where-after, the organization (Eskom) developed a competency framework for project managers.